Mesenchymal Stem Cell Secretome: Cell-free Therapeutic Strategy in Regenerative Medicine - Anna Meiliana; Nurrani Mustika Dewi; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2019)
BACKGROUND: Mesenchymal stem (stromal) cells (MSCs) have a multipotent character, able to differentiate into several cell types, thus MSC serve as a cell reservoir for regenerative medicine. MSC therapeutic potency more associated to their immunosuppressive and anti-inflammatory properties rather than the multipotency, by its mechanism to secrete soluble factors with paracrine actions.CONTENT: MSC paracrine function was known to mediated partly by extracellular vesicles (EVs), which were released predominantly from the endosomal compartment contained in MSC secretome. EV contain a cargo bring micro RNA (miRNA), messenger RNA (mRNA), and proteins from their cells of origin, propose EV as a novel alternative to whole cell therapies, regarding the benefit of EV in safety and easier storage compared to the parent cells.SUMMARY: The discovery of EVs including exosomes in MSC secretome as key of stem cells beneficial function lead to the future hope of using cell-free regenerative therapies.KEYWORDS: MSC, secretome, conditioned media, extracellular vesicle, exosome